FIR channel-shortening equalizers for MIMO ISI channels. - Al-Dhahir, N.
Finite-length delay-optimized multi-input multi-output (MIMO) equalizers that optimally shorten the impulse response memory of frequency-selective MIMO channels are derived. The MIMO equalizers are designed to minimize the average energy of the error sequence between the equalized MIMO channel impulse response and an MIMO target impulse response (TIR) with shorter memory. Two criteria for optimizing the MIMO TIR are analyzed and compared. The presented analytical framework encompasses a multitude of previously-studied finite-length equalization techniques
Keywords: FIR channel-shortening equalizers; FIR digital filters; MIMO ISI channels; MIMO target impulse response; MMSE equalizers; Average energy minimization; Computational complexity; Delay-optimized MIMO equalizers; Equalized MIMO channel impulse response; Error sequence; Frequency-selective MIMO channels; Impulse response memory; Matched filtering; Multi-input multi-output equalizers; Noise whitening